In situ metal organic framework (ZIF-8) and Mechanofusion-Assisted MWCNT coating of LiFePO4/C composite material for lithium-ion batteries - Mathur, Priyatrisha; Shih, Jengywan; James Li, Ying Jeng; Hung, Tai-Feng; Thirumalraj, Balamurugan; Kannan Ramaraj, Sayee; Jose, Rajan; Karuppiah, Chelladurai; Yang, Chunchen (MDPI, 2023)
LiFePO4 is one of the industrial, scalable cathode materials in lithium-ion battery production, due to its cost-effectiveness and environmental friendliness. However, the electrochemical performance of LiFePO4 in high current rate operation is still limited, due to its poor ionic- and electron-conductive properties. In this study, a zeolitic imidazolate framework (ZIF-8) and multiwalled carbon nanotubes (MWCNT) modified LiFePO4/C (LFP) composite cathode materials were developed and investigated in detail. The ZIF-8 and MWCNT can be used as ionic- and electron-conductive materials, respectively. The surface modification of LFP by ZIF-8 and MWCNT was carried out through in situ wet chemical and mechanical alloy coating. The as-synthesized materials were scrutinized via various characterization methods, such as XRD, SEM, EDX, etc., to determine the material microstructure, morphology, phase, chemical composition, etc. The uniform and stable spherical morphology of LFP composites was obtained when the ZIF-8 coating was processed by the agitator [A], instead of the magnetic stirrer [MS], condition. It was found that the (optimum of) 2 wt.% ZIF-8@LFP [A]/MWCNT composite cathode material exhibited outstanding improvement in high-rate performance; it maintained the discharge capacities of 125 mAh g−1 at 1C, 110 mAh g−1 at 3C, 103 mAh g−1 at 5C, and 91 mAh g−1 at 10C. Better cycling stability with capacity retention of 75.82% at 1C for 100 cycles, as compared to other electrodes prepared in this study, was also revealed. These excellent results were mainly obtained because of the improvement of lithium-ion transport properties, less polarization effect, and interfacial impedance of the LFP composite cathode materials derived from the synergistic effect of both ZIF-8 and MWCNT coating materials.